Construction of geographical knowledge in quilombola school education: participatory cartography as a methodological didactic path - Rocha, Brenda Thaís Galdino; Gorayeb, Adryane; Chaves, Leilane Oliveira; Sucupira, Thania Gorayeb (Geosaberes; Vol 9 No 17 (2018): Jan - Apr, 2017)
The present study synthesizes the experience, evaluation and reflection of the didactic-pedagogical proposal of Participative Cartography in the teaching of Geography for Quilombola School Education. The intervention was applied in E.M.E.F. Olímpio Nogueira Lopes in Quilombo Alto Alegre in Horizonte - Ceará, and focused on the collective and participatory construction of maps using the overlay technique, using satellite images and polyester paper to represent the elements to be mapped. It is noteworthy that the construction of the Participatory Cartography in the school is a potential didactic tool to learn the conceptual and procedural knowledge of Cartography, besides, and above all, to have been an instrument to know, recognize and re-signify the knowledge about the territory, quilombola knowledge and traditions in the School space.
Keywords: Educação Escolar Quilombola; Ensino de Geografia; Cartografia Participativa